المعاش النفسي لدى المراهق المقبل على اجتياز امتحان شهادة التعليم المتوسط دراسة ميدانية لحالات باحدى متوسطات ولاية المسيلة - ياسمينة, بورقبة (كلية العلوم الانسانية والاجتماعية جامعة محمد بوضياف المسيلة, 2023)
هدفت هذه الدراسة لمعرفة بماذا يتميز المعاش النفسي لدى المراهقين المقبلين على اجتياز امتحان شهادة التعليم المتوسط عبر المقابلة النصف موجهة ومقياس القلق ل "تايلور"، مقياس الاكتئاب "بيك" ومقياس الشعور بالذنب"عبد العظيم حمدي عبد الله".وتحقيقا لهذه الأهداف تم إتباع المنهج العيادي القائم على تقنية دراسة حالة، حيث بلغت مجموعة الدراسة حالتين (ذكر، أنثى) تم اختيارها بطريقة قصدية كانت أعمارهم 15 سنة من مراهقين مقبلين على اجتياز امتحان شهادة التعليم المتوسط ،بغية الإجابة على التساؤلات التالية: 1- هل يتميز المعاش النفسي للمراهق المقبل على اجتياز امتحان شهادة التعليم المتوسط بالقلق؟ 2- هل يتميز المعاش النفسي للمراهق المقبل على اجتياز امتحان شهادة التعليم المتوسط بالاكتئاب؟ 3-هل يتميز المعاش النفسي للمراهق المقبل على اجتياز امتحان شهادة التعليم المتوسط بالشعور بالذنب؟ بعد تحليل المقابلات وعرض نتائج تطبيق المقاييس،أسفرت الدراسة إلى النتائج الآتية: 1-يتميز المعاش النفسي للمراهق المقبل على اجتياز امتحان شهادة التعليم المتوسط بالقلق من خلال مؤشرات الخوف والتوتر. 2- يتميز المعاش النفسي للمراهق المقبل على اجتياز شهادة التعليم المتوسط بالاكتئاب.من خلال مؤشرات الحزن والأسى وهبوط النشاط. 3- يتميز المعاش النفسي للمراهق على اجتياز امتحان شهادة التعليم المتوسط بالشعور بالذنب،من خلال لوم ونقد الذات. Abstract of study : this study aimed to find out .what distinguishes the psychological pension of adolescents who are about to pass the intermediate education certificate exam through the semi-directed interview, the Taylor anxiety scale, the Beck subscription scale, and the ABDELADIM HAMDI ABDULLAH guilt scall. To achieve these goals, the clinical approach based on A case study technique, were the study group consisted of tow case(male, female) that were deliberately chosen, their ages were years old, from adolescents about to pass the intermediate education certificate exam in order to answer the questions: 1-is the psychological of pension of the teenager who is about to pass the intermediate education certificate exam characterized by anxiety?. 2-is the psychological of the teenager persen who is about to pass the intermediate education certificate exam characterized by depressed? 3-is the psychological pension of a teenager who is about to pass the intermediate education certificate exam characterized by a feeling of guilt? After analyzing the interviews and presenting the results of applying the scales, the study resulted in the following results: 1-the psychological of pension of the teenager who is about to pass the intermediate education certificate exam is characterized by anxiety tension fear and stress. 2- the psychological of the teenager persen who is about to pass the intermediate education certificate exam is characterized by depression through the in indicators of sadness ,distress and decreased activity. 3-is the psychological pension of a teenager who is about to pass the intermediate education certificate exam is characterized by a sense of guilt through indication of criticism and self- blame.